Preparation method of light-colored light-absorbing and heating composite fiber
By reacting modified nano zinc oxide and nano titanium oxide powder with cyclohexane carboxylic acid, polyamide fibers and polyester fibers supported by nano zinc oxide and nano titanium oxide, combined with melt spinning technology, light-colored light-absorbing and heating composites were prepared. Fiber solves the problems of dark color and poor antibacterial and antibacterial effects of light-absorbing and heating fibers, and improves the effects of light-absorbing and heating, radiation-resistant and sterilization.
Patent Information
- Application Number
- CN202411679037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing light-absorbing heating fibers have dark colors, which limit the aesthetics of textiles, and have poor antibacterial and anti-molding effects in the fillings of the cushion and pillow core.
By reacting modified nano zinc oxide and modified nano titanium oxide powder with cyclohexane carboxylic acid, ethanol, acetic acid and other substances, polyamide fibers and polyester fibers loaded with nano zinc oxide and nano titanium oxide are generated, combined with melt spinning Technology prepares Rice-shaped composite fibers to achieve light absorption, heat generation, radiation resistance and sterilization effects.
The light-colored light-absorbing and heating composite fibers have good light-absorbing and heating properties, antibacterial and antibacterial effects, and are easy to dye. They overcome the problem of dark color of traditional light-absorbing and heating fibers and are suitable for fillings of the quilt core and pillow core.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite fibers, and in particular to a method for preparing a light-colored light-absorbing and heat-generating composite fiber. Background Art
[0002] Light-absorbing heat-generating fibers have become a major direction for developing new functional fibers because of their ability to absorb external radiation energy and convert it into heat energy. However, existing mainstream energy-storage heat-generating fibers such as carbon and zirconium carbide are usually dark colors such as black and dark gray, so that the various products made from them can only be darker colors, resulting in problems such as single style and difficulty in dyeing, which limits the aesthetic properties of textiles.
[0003] Patent application document CN116043354A discloses a light-colored thermal insulation fiber and its preparation method, which is made of light-absorbing and heating masterbatch and fiber-forming polymer. By adjusting the raw material composition, content and process, the problem of dark color of traditional light-absorbing and heating fibers is solved, and the influence of fiber color on fabric color is avoided. However, the light-absorbing and heating material used is still a dark nano-ceramic material. By controlling its usage, the influence of dark light-absorbing and heating material on fiber color is reduced. Although this makes the fiber color lighter, the thermal insulation performance is not well guaranteed, and when it is used as a filling material for quilt cores and pillow cores, the antibacterial, antibacterial, deodorizing and mildew-proof effects do not meet the requirements of consumers.
[0004] Therefore, the present invention provides a method for preparing a light-colored light-absorbing and heat-generating composite fiber which is extremely suitable for manufacturing fillings for quilt cores and pillow cores and has light-absorbing and heat-generating, antibacterial and anti-bacterial, and odor-removing and mildew-proof effects. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a light-colored light-absorbing and heat-generating composite fiber to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a light-colored light-absorbing and heat-generating composite fiber comprises the following preparation steps: (1) The modified nano zinc oxide powder and cyclohexane carboxylic acid are mixed in a mass ratio of 2 to 3:1 to obtain a mixture, which is dissolved in an ether solution 3 to 5 times the mass of the mixture, and then 0.05 to 0.1 times the mass of p-toluenesulfonic acid is added, and ultrasonication is performed at 30 to 40 kHz for 80 to 100 minutes. The temperature is raised to 78 to 79°C, and the mixture is stirred at 700 to 800 r / min for 6 to 8 hours. The precipitate is filtered to obtain a precipitate, and 80 wt% acetic acid solution 3 to 5 times the mass of the precipitate and cobalt acetate 0.04 to 0.15 times the mass of the cyclohexane substance are added, and then 0.5 to 1 times the mass of the precipitate is added with a 50 wt% acetaldehyde solution, and the mixture is stirred at 300 to 500 r / min for 30 to 60 minutes. The mixture is reacted at 90°C and 1.8 MPa for 9 hours, and the mixture is filtered while hot to obtain a solid. The mixture is filtered while hot to obtain a solid, and the solid is dried at 100°C for 24 hours to obtain adipic acid loaded with nano zinc oxide particles. (2) Adipic acid, hexamethylenediamine and ethanol loaded with nano zinc oxide particles were mixed in a mass ratio of 1.5:2:3, heated to 60-70°C, stirred at 100-150 r / min for 3 h, filtered, the precipitate was taken, washed with ethanol for 3-5 times, dried at 80°C for 24 h, and deionized water was added to prepare a 63 wt% aqueous solution; (3) The aqueous solution is introduced into a static mixer, and an ethylenediamine acetic acid solution of 0.5 to 0.6 times the mass of the aqueous solution is added, wherein the molar ratio of hexamethylenediamine to acetic acid in the ethylenediamine acetic acid solution is 3:5, and then placed in an evaporation reactor, evaporated for 3 hours at 232°C, 1.72MPa and nitrogen protection, and then entered into a tubular reactor and heated to 285°C, reacted for 40 to 45 minutes, and the pressure was reduced to 0.28MPa for extrusion, and then entered into a finished product reactor, the pressure was reduced to 40kPa, the temperature was reduced to 270 to 272°C, the reaction was 50 to 55 minutes, and the modified polyamide fiber slices were obtained; (4) The modified nano titanium oxide powder and 2,5-dimethylphenol were mixed at a mass ratio of 2.2-2.5:1, phosphorus trichloride (0.6-0.8 times the mass of the mixed solution) was added, and the mixture was stirred at 700-800 r / min for 48 h. The oil bath was heated to 130-135°C and the reaction was carried out for 6-8 h. After the reaction, the temperature was lowered to 110-120°C, and a 5 wt% sodium bicarbonate aqueous solution (3-5 times the total mass of the reaction solution) was poured in. After reacting for 2-3 h, the mixture was filtered and the precipitate was taken out. After drying at 60-80°C for 24 h, the precipitate was recrystallized with ethanol (1.5-2 times the mass of the precipitate), filtered, and dried at 60-80°C for 24 h to obtain 2,5-dimethylbenzene loaded with nano titanium oxide powder. (5) 2,5-dimethylbenzene loaded with nano-titanium oxide powder and MC catalyst were poured into a high-pressure reactor at a mass ratio of 15-20:1. After nitrogen ventilation for 3 times, oxygen was filled in at room temperature to a pressure of 1 MPa. The oil bath was heated to 90-95°C, stirred at 500-600 r / min, reacted for 4 hours, cooled naturally to room temperature, filtered, and the precipitate was washed 3 times with acetic acid 1.5-2 times the mass of the precipitate, and dried at 100°C for 24 hours to obtain terephthalic acid loaded with nano-titanium oxide powder; (6) Ethylene glycol and terephthalic acid loaded with nano-titanium oxide powder are mixed in a mass ratio of 1.05-1.15:1 to obtain a mixed solution, antimony acetate in an amount 3-5 times the mass of the mixed solution is added, and the mixture is stirred at 200-300 r / min for 2 hours; then the temperature is raised to 255-257°C, the pressure is raised to 140 kPa, and the reaction is continued for 6 hours; the temperature is further raised to 264-266°C, the pressure is reduced to 110 kPa, and the reaction is continued for 90 minutes; then the temperature is further raised to 272-274°C, the pressure is reduced to 10 kPa, and the reaction is continued for 40 minutes; the temperature is further raised to 375-377°C, the pressure is reduced to 1 kPa, and the reaction is continued for 50 minutes; the temperature is further reduced to 284-286°C, the pressure is reduced to 0.14 kPa, and the reaction is continued for 180 minutes, and the mixture is extruded at 284-286°C, dried at 60-80°C, and sliced to obtain modified polyester fiber slices; (7) The pretreated modified polyamide fiber slices and the pretreated modified polyester fiber slices are melt-spun at a mass ratio of 82:18, cooled and formed to obtain a light-colored light-absorbing and heat-generating composite fiber.
[0007] Furthermore, the modified nano zinc oxide powder in step (1) comprises the following preparation steps: 1) Take 20~30mg candle ash and 40~60g sodium hydroxide and stir at 80~100r / min for 20~30min, add 40mL secondary deionized water, stir at 80~100r / min for 20~30min, and ultrasonicate at 30~40kHz for 30~60min to obtain a reaction solution. Put the reaction solution into a hot air drying oven, heat it to 200℃ and keep it at a constant temperature for 10~15h, and then cool it naturally to room temperature; centrifuge at 9000~12000r / min for 3~5h to remove the precipitate, adjust the pH to 7~8 with 37wt% hydrochloric acid solution, and then filter it with a 0.20~0.25um filter membrane to obtain a filtrate. The filtrate is filtered with MWCO The 3500 dialysis bag was dialyzed in 4L secondary deionized water for 6~8h, and then 4L secondary deionized water was replaced and dialyzed for another 6~8h to obtain a carbon dot solution; the carbon dot solution was dried at 80℃ and 40~50kPa for 24~30h to prepare a 190~200mg / L carbon dot solution; 2) Dissolve 10-15 mmol zinc nitrate hexahydrate and 10-15 mmol oxalic acid dihydrate in 20-30 mL anhydrous ethanol solution, stir at 200-300 r / min for 4-6 h until completely dissolved, then pour the mixed solution containing oxalic acid into the zinc nitrate mixed solution while stirring at 200-300 r / min, heat to 120-150 ° C for 9-12 h, cool to room temperature, collect the solid by centrifugation, wash with deionized water 2-3 times, then wash with anhydrous ethanol 2-3 times, dry at 80 ° C for 20-30 h, calcine the dried solid at 420 ° C for 2-3 h, and naturally cool to room temperature to obtain pure phase porous zinc oxide nanorods; 3) Take 10 g of porous zinc oxide nanorods and dissolve them in 50 mL of distilled water, ultrasonicate them at 30-40 kHz for 10-30 min, add carbon dot solution until the mass fraction of the carbon dot solution is 0.2%-2%, stir at 300-400 r / min for 3-6 h, then wash and centrifuge at 8000-10000 r / min for 3-5 h, and then dry at 100° C. for 10-15 h to obtain the modified nano zinc oxide powder.
[0008] Furthermore, the modified nano titanium oxide powder in step (4) comprises the following preparation steps: a. Place 10 g of titanium oxide powder with a particle size of 100 nm in a vacuum drying oven at 120-130°C and 50-60 kPa for 2-3 hours, then place in 100 mL of anhydrous ethanol solution, and disperse at 30-40 kHz ultrasonic wave for 30-60 minutes to obtain a dispersed nano-titanium oxide ethanol solution; b. Dissolve 5-20 mg of KH570 in 100 mL of deionized water and hydrolyze for 30-60 min to obtain a KH570 aqueous solution. Completely mix the nano titanium oxide ethanol solution obtained in step a and the KH570 aqueous solution obtained above, adjust the pH to 4 with a 35 wt % acetic acid aqueous solution, centrifuge at 10000-12000 r / min for 20-30 min, take the solid, place it in 200-300 mL of deionized water, ultrasonicate at 30-40 kHz for 10-30 min, centrifuge at 10000-12000 r / min for 20-30 min, take the solid, dry it at 100-120 ° C for 20-30 h, and cool it to room temperature under a vacuum of 40-50 kPa to obtain a modified nano titanium oxide powder.
[0009] Furthermore, the preparation method of the MC catalyst in step (5) is as follows: Co(OAc)2, Mn(OAc)2 and NaBr are mixed in a molar ratio of 0.13-0.18:0.029-0.033:1, and then dissolved in an acetic acid solution with a total mass of 4.1-4.4 times.
[0010] Furthermore, the pretreated modified polyester fiber chips in step (7) are obtained by pre-crystallizing the modified polyester fiber chips at 150-200° C. and then drying them with dry air having a dew point of -82° C., at a drying temperature of 130-180° C., and for a drying time of 6-12 hours.
[0011] Furthermore, the pretreated modified polyamide fiber slices in step (7) are obtained by drying the modified polyamide fiber slices at a drying temperature of 80 to 100° C. for 4 hours.
[0012] Furthermore, in step (7), the flow process of the pretreated modified polyamide fiber and the pretreated modified polyester fiber melt in the spinning assembly is as follows: the pretreated modified polyamide fiber flows through the plum blossom channel, and the pretreated modified polyester fiber flows through the hole channel.
[0013] Furthermore, in step (7), the spinning temperature of the pretreated polyamide fiber is 260-270° C. and the pressure is 13-15 MPa, and the spinning temperature of the pretreated polyester fiber is 285-295° C. and the pressure is 15-17 MPa.
[0014] Furthermore, the spinning speed of the melt spinning in step (7) is 2800-3300 m / min.
[0015] Furthermore, the specific conditions for the cooling forming in step (7) are: side wind cooling with a wind speed of 0.40-0.65 m / min and a wind temperature of 18-22°C.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention prepares the cross-shaped composite fiber through the steps of modified polyester fiber preparation, modified polyamide fiber preparation, melt spinning, cooling and forming, so as to achieve the performance of light absorption, heat generation, radiation resistance and sterilization.
[0017] First, the nano zinc oxide particles are modified by carbon dot solution, so that the number of active hydroxyl groups on the surface of the zinc oxide nanoparticles increases. The active hydroxyl groups on the surface of the zinc oxide nanoparticles react with cyclohexane carboxylic acid to undergo an esterification reaction, and then the catalytic property of the carbon dot-zinc oxide is used to catalytically oxidize the cyclohexane structure in the cyclohexane carboxylic acid to generate adipic acid, which is then polymerized with hexamethylenediamine to generate polyamide fibers loaded with zinc oxide nanoparticles. The zinc oxide nanoparticles are first introduced and then polymerized to generate fibers, which overcomes the problem of easy agglomeration of the zinc oxide nanoparticles themselves, making the zinc oxide nanoparticles more evenly distributed in the polyamide fiber. Nano zinc oxide has a strong ability to absorb infrared light, and can even absorb the heat emitted by the human body, with good heating and heat storage effects. It also has a series of unique properties such as antibacterial and antibacterial, deodorizing and mildew-proofing. In addition, it is white in color and has a low diffuse reflectivity to light, which is easy to dye, overcoming the shortcomings of conventional light-absorbing and heating fabrics that are dark in color and unsightly.
[0018] Secondly, titanium oxide nanoparticles were modified with KH570 to increase the number of active carboxyl groups on the surface of titanium oxide nanoparticles. The active carboxyl groups on the surface of titanium oxide nanoparticles reacted with 2,5-dimethylphenol to undergo esterification reaction, and then catalytic oxidation of the p-xylene structure in 2,5-dimethylphenol was performed to generate terephthalic acid, which was then polycondensed with ethylene glycol to generate polyester fibers loaded with titanium oxide nanoparticles. The introduction of nano titanium oxide particles can make up for the deficiency of nano zinc oxide in ultraviolet radiation absorption. Polyester fibers also have excellent wrinkle resistance and shape retention, as well as high strength and elastic recovery, making the woven fabrics durable and able to quickly recover to their original state. The M-shaped composite fiber formed by the composite of modified polyester fiber and modified polyamide fiber can well overcome the shortcomings of poor dyeability and poor air permeability, and has the advantages of both. Moreover, the M-shaped composite fiber has both the softness of fan-shaped ultrafine fibers and the rigidity and stiffness of "M"-shaped skeleton materials, which is very suitable for making fillings for quilt cores and pillow cores. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the light-colored light-absorbing and heat-generating composite fibers prepared in the following examples are as follows: Dyeing rate: The dyeing effect of the embodiment and the comparative example of the same size was tested, and the fiber surface dyeing was tested according to the GB / T23976.1-2009 standard.
[0021] Maximum temperature rise value and average temperature rise value: Take the same size of the embodiment and the comparative example to test the heating effect, and determine the fiber surface temperature rise according to GB / T18319-2019 standard. Use sunlight as the irradiation light source. The sample absorbs light energy and causes the temperature to change. Use a temperature sensor to test the sample temperature, and record the temperature change of the sample per minute within 10 minutes of irradiation and 10 minutes of turning off the light source.
[0022] Breaking strength: The flame retardant effect of the embodiment and the comparative example of the same size was tested according to GB / T3923.1-2013 Textiles, Fiber Elongation and Tensile Breaking Strength Standard.
[0023] Antibacterial performance: The antibacterial performance of the embodiment and the comparative example of the same size was tested according to the AATCC100-2012 "Evaluation of Antibacterial Finishing of Textile Materials" standard.
[0024] Anti-radiation performance: The antibacterial performance of the embodiment and the comparative example of the same size was tested according to the standard GB / T 18830 "Evaluation of the UV protection performance of textiles".
[0025] Example 1; (1) 20 mg of candle ash and 40 g of sodium hydroxide were stirred at 80 / min for 20 min, 40 mL of secondary deionized water was added, the mixture was stirred at 80 r / min for 20 min, and ultrasonicated at 30 kHz for 30 min to obtain a reaction solution, the reaction solution was placed in a hot air drying oven, heated to 200°C and kept at this temperature for 10 h, and then naturally cooled to room temperature; the precipitate was removed by centrifugation at 9000 r / min for 3 h, the pH was adjusted to 7 with a 37 wt % hydrochloric acid solution, and then filtered with a 0.20 um filter membrane to obtain a filtrate, the filtrate was dialyzed in 4 L of secondary deionized water with a MWCO 3500 dialysis bag for 6 h, 4 L of secondary deionized water was replaced, and the carbon dot solution was dialyzed for another 6 h to obtain a carbon dot solution; the carbon dot solution was dried at 80°C and 40 kPa for 24 h, and a 190 mg / L carbon dot solution was prepared; (2) Dissolve 10 mmol of zinc nitrate hexahydrate and 10 mmol of oxalic acid dihydrate in 20 mL of anhydrous ethanol solution, stir at 200 r / min for 4 h until completely dissolved, then pour the mixture containing oxalic acid into the zinc nitrate mixture while stirring at 200 r / min, heat to 120 °C for 9 h, cool to room temperature, collect the solid by centrifugation, wash twice with deionized water, then wash twice with anhydrous ethanol, dry at 80 °C for 20 h, calcine the dried solid at 420 °C for 2 h, and cool naturally to room temperature to obtain pure phase porous zinc oxide nanorods; (3) 10 g of porous zinc oxide nanorods were placed in 50 mL of distilled water, ultrasonicated at 30 kHz for 10 min, and carbon dot solution was added until the mass fraction of the carbon dot solution was 0.2%. The mixture was stirred at 300 r / min for 3 h, then washed and centrifuged at 8000 r / min for 3 h, and then dried at 100 °C for 10 h to obtain modified nano zinc oxide powder. (4) The modified nano zinc oxide powder and cyclohexane carboxylic acid were mixed in a mass ratio of 2:1 to obtain a mixture, which was dissolved in an ether solution 3 times the mass of the mixture, and then 0.05 times the mass of p-toluenesulfonic acid was added. The mixture was ultrasonicated at 30kHz for 80 minutes, heated to 78°C, stirred at 700 r / min for 6 hours, filtered to obtain a precipitate, and then 80wt% acetic acid solution 3 times the mass of the precipitate and cobalt acetate 0.04 times the amount of cyclohexane substance were added, and then 0.5 times the mass of the precipitate was added with 50wt% acetaldehyde solution, stirred at 300 r / min for 30 minutes, reacted at 90°C and 1.8MPa for 9 hours, filtered while hot, and the solid was taken out and dried at 100°C for 24 hours to obtain adipic acid loaded with nano zinc oxide particles; (5) Adipic acid, hexamethylenediamine and ethanol loaded with nano zinc oxide particles were mixed in a mass ratio of 1.5:2:3, heated to 60°C, stirred at 100 r / min for 3 h, filtered, the precipitate was taken, washed with ethanol for 3 times, dried at 80°C for 24 h, and deionized water was added to prepare a 63 wt% aqueous solution; (6) The aqueous solution is introduced into a static mixer, and an ethylenediamine acetic acid solution of 0.5 times the mass of the aqueous solution is added, wherein the molar ratio of hexamethylenediamine to acetic acid in the ethylenediamine acetic acid solution is 3:5. The aqueous solution is then placed into an evaporation reactor, and evaporated for 3 hours at 232°C, 1.72 MPa and nitrogen protection. The aqueous solution is then placed into a tubular reactor and heated to 285°C, reacted for 40 minutes, and the pressure is reduced to 0.28 MPa for extrusion. The aqueous solution is then placed into a finished product reactor, and the pressure is reduced to 40 kPa, and the temperature is reduced to 270°C, and the reaction is carried out for 50 minutes. The aqueous solution is extruded at 270°C, dried at 60°C for 20 hours, and sliced to obtain modified polyamide fiber slices. (7) 10 g of titanium oxide powder with a particle size of 100 nm was placed in a vacuum drying oven at 120°C and 50 kPa for 2 h, then placed in 100 mL of anhydrous ethanol solution and dispersed at 30 kHz ultrasonic wave for 30 min to obtain a dispersed nano-titanium oxide ethanol solution; (8) Dissolve 5 mg of KH570 in 100 mL of deionized water and hydrolyze for 300 min to obtain a KH570 aqueous solution. Completely mix the nano-titanium oxide ethanol solution obtained in step a and the KH570 aqueous solution obtained above, adjust the pH to 4 with a 35 wt % acetic acid aqueous solution, centrifuge at 10,000 r / min for 20 min, take the solid, place it in 200 mL of deionized water, ultrasonicate at 30 kHz for 10 min, and then centrifuge at 10,000 r / min for 20 min. Take the solid, dry it at 100 ° C for 20 h, and cool it to room temperature under 40 kPa vacuum to obtain a modified nano-titanium oxide powder; (9) The modified nano titanium oxide powder was mixed with 2,5-dimethylphenol at a mass ratio of 2.2:1, and phosphorus trichloride (0.6 times the mass of the mixed solution) was added. The mixture was stirred at 700 r / min for 48 h, and the oil bath was heated to 130°C for 6 h. After the reaction, the temperature was lowered to 110°C, and a 5 wt% sodium bicarbonate aqueous solution (3 times the total mass of the reaction solution) was poured in. After reacting for 2 h, the mixture was filtered, the precipitate was taken, dried at 60°C for 24 h, and recrystallized with ethanol (1.5 times the mass of the precipitate), filtered, and dried at 60°C for 24 h to obtain 2,5-dimethylbenzene loaded with nano titanium oxide powder; (10) 2,5-dimethylbenzene loaded with nano-titanium oxide powder and MC catalyst were poured into a high-pressure reactor in a mass ratio of 15:1. After nitrogen ventilation for 3 times, oxygen was filled in at room temperature until the pressure reached 1 MPa. The oil bath was heated to 90°C, stirred at 500 r / min, reacted for 4 hours, naturally cooled to room temperature, filtered, and the precipitate was taken. After washing with acetic acid 1.5 times the mass of the precipitate for 3 times, it was dried at 100°C for 24 hours to obtain terephthalic acid loaded with nano-titanium oxide powder. The preparation method of the MC catalyst is as follows: Co(OAc)2, Mn(OAc)2 and NaBr were mixed in a molar ratio of 0.13:0.029:1, and dissolved in acetic acid 4.1 times the total mass. (11) Ethylene glycol and terephthalic acid loaded with nano-titanium oxide powder were mixed in a mass ratio of 1.05:1 to obtain a mixed solution, antimony acetate 3 times the mass of the mixed solution was added, and the mixture was stirred at 200 r / min for 2 hours; then the temperature was raised to 255°C, the pressure was raised to 140 kPa, and the reaction was continued for 6 hours; the temperature was further raised to 264°C, the pressure was reduced to 110 kPa, and the reaction was continued for 90 minutes; then the temperature was further raised to 272°C, the pressure was reduced to 10 kPa, and the reaction was continued for 40 minutes; the temperature was further raised to 375°C, the pressure was reduced to 1 kPa, and the reaction was continued for 50 minutes; the temperature was reduced to 284°C, the pressure was reduced to 0.14 kPa, and the reaction was continued for 180 minutes, and the mixture was extruded at 284°C, dried at 60°C, and sliced to obtain modified polyester fiber slices; (12) The modified polyester fiber slices were pre-crystallized at 150°C, and then dried with dry air with a dew point of -82°C, the drying temperature was 130°C, and the drying time was 6 hours to obtain the pretreated modified polyester fiber slices; the modified polyamide fiber slices were dried at 80°C for 4 hours to obtain the pretreated modified polyamide fiber slices; the pretreated modified polyamide fiber slices and the pretreated modified polyester fiber slices were melt-spun at a mass ratio of 82:18, and the pretreated modified polyamide fiber and the pretreated modified poly The flow process of the ester fiber melt in the spinning assembly is as follows: the pretreated modified polyamide fiber goes through the plum blossom groove channel, the pretreated modified polyester fiber goes through the hole channel, and the spinning speed is 2800m / min; the spinning temperature of the pretreated polyamide fiber is 260℃, and the pressure is 13MPa, and the spinning temperature of the pretreated polyester fiber is 285℃, and the pressure is 15MPa; and then it is cooled and formed by side wind cooling with a wind speed of 0.40m / min and a wind temperature of 18℃ to obtain a light-colored light-absorbing and heat-generating composite fiber.
[0026] Example 2; (1) 25 mg of candle ash and 50 g of sodium hydroxide were stirred at 90 r / min for 25 min, 40 mL of secondary deionized water was added, the mixture was stirred at 90 r / min for 25 min, and ultrasonicated at 35 kHz for 45 min to obtain a reaction solution. The reaction solution was placed in a hot air drying oven, heated to 200°C and kept at this temperature for 13 h, and then naturally cooled to room temperature; the precipitate was removed by centrifugation at 10000 r / min for 4 h, the pH was adjusted to 7 with a 37 wt % hydrochloric acid solution, and then filtered with a 0.23 um filter membrane to obtain a filtrate, the filtrate was dialyzed in 4 L of secondary deionized water with a MWCO 3500 dialysis bag for 7 h, 4 L of secondary deionized water was replaced, and the carbon dot solution was dialyzed for another 7 h; the carbon dot solution was dried at 80°C and 45 kPa for 28 h, and a 195 mg / L carbon dot solution was prepared; (2) Dissolve 12 mmol of zinc nitrate hexahydrate and 12 mmol of oxalic acid dihydrate in 25 mL of anhydrous ethanol solution, stir at 250 r / min for 5 h until completely dissolved, then pour the mixture containing oxalic acid into the zinc nitrate mixture while stirring at 250 r / min, heat to 135 °C for 10 h, cool to room temperature, collect the solid by centrifugation, wash twice with deionized water, then wash three times with anhydrous ethanol, dry at 80 °C for 25 h, calcine the dried solid at 420 °C for 2 h, and naturally cool to room temperature to obtain pure phase porous zinc oxide nanorods; (3) Take 10 g of porous zinc oxide nanorods and dissolve them in 50 mL of distilled water. Ultrasonicate at 35 kHz for 20 min, add carbon dot solution until the mass fraction of the carbon dot solution is 1%, stir at 350 r / min for 5 h, then wash and centrifuge at 9000 r / min for 4 h, and then dry at 100 °C for 12 h to obtain modified nano zinc oxide powder.
[0027] (4) The modified nano zinc oxide powder and cyclohexane carboxylic acid were mixed at a mass ratio of 2.5:1 to obtain a mixture, which was dissolved in an ether solution 4 times the mass of the mixture, and then 0.07 times the mass of p-toluenesulfonic acid was added. The mixture was ultrasonicated at 35kHz for 90 minutes, heated to 78°C, stirred at 750r / min for 7 hours, filtered to obtain a precipitate, and then 4 times the mass of the precipitate was added with 80wt% acetic acid solution and 0.1 times the amount of cyclohexane substance. Cobalt acetate, 0.6 times the mass of the precipitate was added, stirred at 400r / min for 45 minutes, and reacted at 90°C and 1.8MPa for 9 hours. The solid was taken out by suction and dried at 100°C for 24 hours to obtain adipic acid loaded with nano zinc oxide particles. (5) Adipic acid, hexamethylenediamine and ethanol loaded with nano zinc oxide particles were mixed in a mass ratio of 1.5:2:3, heated to 65°C, stirred at 125 r / min for 3 h, filtered, the precipitate was taken, washed with ethanol 4 times, dried at 80°C for 24 h, and deionized water was added to prepare a 63 wt% aqueous solution; (6) The aqueous solution is pumped into a static mixer, and an ethylenediamine acetic acid solution of 0.55 times the mass of the aqueous solution is added, wherein the molar ratio of hexamethylenediamine to acetic acid in the ethylenediamine acetic acid solution is 3:5. The aqueous solution is then placed in an evaporation reactor, evaporated for 3 hours at 232°C, 1.72 MPa and nitrogen protection, and then enters a tubular reactor and is heated to 285°C, reacted for 42 minutes, and the pressure is reduced to 0.28 MPa for extrusion. The aqueous solution enters a finished product reactor, the pressure is reduced to 40 kPa, the temperature is reduced to 271°C, the reaction is performed for 53 minutes, extruded at 271°C, dried at 70°C for 25 hours, and sliced to obtain modified polyamide fiber slices; (7) 10 g of titanium oxide powder with a particle size of 100 nm was placed in a vacuum drying oven at 125°C and 55 kPa for 2.5 h, then placed in 100 mL of anhydrous ethanol solution and dispersed by 35 kHz ultrasonic wave for 45 min to obtain a dispersed nano-titanium oxide ethanol solution; (8) Dissolve 10 mg of KH570 in 100 mL of deionized water and hydrolyze for 45 min to obtain a KH570 aqueous solution. Completely mix the nano-titanium oxide ethanol solution obtained in step a with the KH570 aqueous solution obtained above, adjust the pH to 4 with a 35 wt % acetic acid aqueous solution, centrifuge at 11000 r / min for 25 min, take the solid, place it in 250 mL of deionized water, ultrasonicate at 35 kHz for 25 min, and then centrifuge at 11000 r / min for 25 min. Take the solid, dry it at 110° C. for 25 h, and cool it to room temperature under 45 kPa vacuum to obtain a modified nano-titanium oxide powder. (9) The modified nano titanium oxide powder was mixed with 2,5-dimethylphenol at a mass ratio of 2.3:1, and phosphorus trichloride (0.7 times the mass of the mixed solution) was added, stirred at 750 r / min for 48 h, heated to 133 °C in an oil bath, reacted for 7 h, cooled to 115 °C after the reaction, and 5 wt% sodium bicarbonate aqueous solution (4 times the total mass of the reaction solution) was poured in. After reacting for 2.5 h, the mixture was filtered, the precipitate was taken, dried at 70 °C for 24 h, and recrystallized with ethanol (1.7 times the mass of the precipitate), filtered, and dried at 70 °C for 24 h to obtain 2,5-dimethylbenzene loaded with nano titanium oxide powder; (10) 2,5-dimethylbenzene loaded with nano-titanium oxide powder and MC catalyst were poured into a high-pressure reactor in a mass ratio of 17:1. After nitrogen ventilation for 3 times, oxygen was filled in at room temperature until the pressure reached 1 MPa. The oil bath was heated to 92°C, stirred at 550 r / min, reacted for 4 hours, naturally cooled to room temperature, filtered, and the precipitate was taken. After washing with acetic acid 1.6 times the mass of the precipitate for 3 times, it was dried at 100°C for 24 hours to obtain terephthalic acid loaded with nano-titanium oxide powder. The preparation method of the MC catalyst is as follows: Co(OAc)2, Mn(OAc)2 and NaBr were mixed in a molar ratio of 0.16:0.031:1, and dissolved in an acetic acid solution 4.2 times the total mass. (11) Ethylene glycol and terephthalic acid loaded with nano-titanium oxide powder are mixed in a mass ratio of 1.1:1 to obtain a mixed solution, antimony acetate 4 times the mass of the mixed solution is added, and stirred at 200-300 r / min for 2 hours; then the temperature is raised to 256°C, the pressure is raised to 140 kPa, and the reaction is continued for 6 hours; the temperature is further raised to 265°C, the pressure is reduced to 110 kPa, and the reaction is continued for 90 minutes; then the temperature is further raised to 273°C, the pressure is reduced to 10 kPa, and the reaction is continued for 40 minutes; the temperature is further raised to 376°C, the pressure is reduced to 1 kPa, and the reaction is continued for 50 minutes; the temperature is reduced to 285°C, the pressure is reduced to 0.14 kPa, and the reaction is continued for 180 minutes, and the modified polyester fiber slices are obtained; (12) The modified polyester fiber slices were pre-crystallized at 170°C, and then dried with dry air with a dew point of -82°C, the drying temperature was 160°C, and the drying time was 9 hours to obtain the pretreated modified polyester fiber slices; the modified polyamide fiber slices were dried at 90°C for 4 hours to obtain the pretreated modified polyamide fiber slices; the pretreated modified polyamide fiber slices and the pretreated modified polyester fiber slices were melt-spun at a mass ratio of 82:18, and the pretreated modified polyamide fiber and the pretreated modified poly The flow process of the ester fiber melt in the spinning assembly is as follows: the pretreated modified polyamide fiber goes through the plum blossom groove channel, the pretreated modified polyester fiber goes through the hole channel, and the spinning speed is 3100m / min; the spinning temperature of the pretreated polyamide fiber is 265℃, and the pressure is 14MPa, and the spinning temperature of the pretreated polyester fiber is 290℃, and the pressure is 16MPa; and then it is cooled and formed by side wind with a wind speed of 0.55m / min and a wind temperature of 20℃ to obtain a light-colored light-absorbing and heat-generating composite fiber.
[0028] Example 3; (1) 30 mg of candle ash and 60 g of sodium hydroxide were stirred at 100 r / min for 30 min, 40 mL of secondary deionized water was added, and the mixture was stirred at 100 r / min for 30 min. The reaction solution was ultrasonically treated at 40 kHz for 60 min to obtain a reaction solution. The reaction solution was placed in a hot air drying oven, heated to 200°C and kept at this temperature for 15 h, and then naturally cooled to room temperature; the precipitate was removed by centrifugation at 12000 r / min for 5 h, the pH was adjusted to 8 with a 37 wt % hydrochloric acid solution, and then filtered with a 0.25 um filter membrane to obtain a filtrate. The filtrate was dialyzed in 4 L of secondary deionized water with a MWCO 3500 dialysis bag for 8 h, and 4 L of secondary deionized water was replaced and dialyzed for another 8 h to obtain a carbon dot solution; the carbon dot solution was dried at 80°C and 50 kPa for 30 h, and a 200 mg / L carbon dot solution was prepared; (2) Dissolve 15 mmol of zinc nitrate hexahydrate and 15 mmol of oxalic acid dihydrate in 30 mL of anhydrous ethanol solution respectively, stir at 300 r / min for 6 h until completely dissolved, then pour the mixed solution containing oxalic acid into the mixed solution of zinc nitrate while stirring at 300 r / min, heat to 150 °C for 12 h, cool to room temperature, collect the solid by centrifugation, wash with deionized water 3 times, then wash with anhydrous ethanol 3 times, dry at 80 °C for 30 h, calcine the dried solid at 420 °C for 3 h, and naturally cool to room temperature to obtain pure phase porous zinc oxide nanorods; (3) Take 10 g of porous zinc oxide nanorods and dissolve them in 50 mL of distilled water. Ultrasonicate at 40 kHz for 30 min, add carbon dot solution until the mass fraction of the carbon dot solution is 2%, stir at 400 r / min for 6 h, then wash and centrifuge at 10000 r / min for 5 h, and then dry at 100 °C for 15 h to obtain modified nano zinc oxide powder.
[0029] (4) The modified nano zinc oxide powder and cyclohexane carboxylic acid were mixed in a mass ratio of 3:1 to obtain a mixture, which was dissolved in an ether solution 5 times the mass of the mixture, and then 0.1 times the mass of p-toluenesulfonic acid was added. The mixture was ultrasonicated at 40kHz for 100 minutes, heated to 79°C, stirred at 800r / min for 8 hours, filtered to obtain a precipitate, and then 5 times the mass of the precipitate was added with 80wt% acetic acid solution and 0.15 times the amount of cyclohexane substance. Cobalt acetate, then 1 times the mass of the precipitate was added with 50wt% acetaldehyde solution, stirred at 500r / min for 60 minutes, reacted at 90°C and 1.8MPa for 9 hours, filtered while hot, and the solid was taken out and dried at 100°C for 24 hours to obtain adipic acid loaded with nano zinc oxide particles; (5) Adipic acid, hexamethylenediamine and ethanol loaded with nano zinc oxide particles were mixed in a mass ratio of 1.5:2:3, heated to 70°C, stirred at 150 r / min for 3 h, filtered, the precipitate was taken, washed with ethanol for 5 times, dried at 80°C for 24 h, and deionized water was added to prepare a 63 wt% aqueous solution; (6) The aqueous solution is pumped into a static mixer, and an ethylenediamine acetic acid solution of 0.6 times the mass of the aqueous solution is added, wherein the molar ratio of hexamethylenediamine to acetic acid in the ethylenediamine acetic acid solution is 3:5. The aqueous solution is then placed in an evaporation reactor, evaporated for 3 hours at 232°C, 1.72 MPa and nitrogen protection, and then enters a tubular reactor and is heated to 285°C, reacted for 45 minutes, and the pressure is reduced to 0.28 MPa for extrusion. The aqueous solution enters a finished product reactor, the pressure is reduced to 40 kPa, the temperature is reduced to 272°C, the reaction is performed for 55 minutes, extruded at 272°C, dried at 80°C for 30 hours, and sliced to obtain modified polyamide fiber slices; (7) 10 g of titanium oxide powder with a particle size of 100 nm was placed in a vacuum drying oven at 130°C and 60 kPa for 3 h, then placed in 100 mL of anhydrous ethanol solution and dispersed by 40 kHz ultrasonic wave for 60 min to obtain a dispersed nano-titanium oxide ethanol solution; (8) Dissolve 20 mg of KH570 in 100 mL of deionized water and hydrolyze for 60 min to obtain a KH570 aqueous solution. Completely mix the nano-titanium oxide ethanol solution obtained in step a with the KH570 aqueous solution obtained above, adjust the pH to 4 with a 35 wt % acetic acid aqueous solution, centrifuge at 12000 r / min for 30 min, take the solid, place it in 300 mL of deionized water, ultrasonicate at 40 kHz for 30 min, and centrifuge at 12000 r / min for 30 min. Take the solid, dry it at 120° C. for 30 h, and cool it to room temperature under 50 kPa vacuum to obtain a modified nano-titanium oxide powder. (9) The modified nano titanium oxide powder was mixed with 2,5-dimethylphenol at a mass ratio of 2.2-2.5:1, phosphorus trichloride (0.8 times the mass of the mixed solution) was added, and the mixture was stirred at 800 r / min for 48 h. The oil bath was heated to 135°C and reacted for 8 h. After the reaction, the temperature was lowered to 120°C, and a 5 wt% sodium bicarbonate aqueous solution (5 times the total mass of the reaction solution) was poured in. After reacting for 3 h, the mixture was filtered, the precipitate was taken, dried at 80°C for 24 h, and recrystallized with ethanol (2 times the mass of the precipitate), filtered, and dried at 80°C for 24 h to obtain 2,5-dimethylbenzene loaded with nano titanium oxide powder; (10) 2,5-dimethylbenzene loaded with nano-titanium oxide powder and MC catalyst were poured into a high-pressure reactor in a mass ratio of 20:1. After nitrogen ventilation for 3 times, oxygen was filled in at room temperature until the pressure reached 1 MPa. The oil bath was heated to 95°C, stirred at 600 r / min, reacted for 4 hours, naturally cooled to room temperature, filtered, and the precipitate was taken. After washing with acetic acid twice the mass of the precipitate for 3 times, it was dried at 100°C for 24 hours to obtain terephthalic acid loaded with nano-titanium oxide powder. The preparation method of the MC catalyst is as follows: Co(OAc)2, Mn(OAc)2 and NaBr were mixed in a molar ratio of 0.18:0.033:1, and dissolved in an acetic acid solution 4.4 times the total mass. (11) Ethylene glycol and terephthalic acid loaded with nano-titanium oxide powder were mixed in a mass ratio of 1.15:1 to obtain a mixed solution, antimony acetate in an amount 5 times the mass of the mixed solution was added, and the mixture was stirred at 300 r / min for 2 h; then the temperature was raised to 257°C, the pressure was raised to 140 kPa, and the reaction was continued for 6 h; the temperature was further raised to 266°C, the pressure was reduced to 110 kPa, and the reaction was continued for 90 min; then the temperature was further raised to 274°C, the pressure was reduced to 10 kPa, and the reaction was continued for 40 min; the temperature was further raised to 377°C, the pressure was reduced to 1 kPa, and the reaction was continued for 50 min; the temperature was reduced to 286°C, the pressure was reduced to 0.14 kPa, and the reaction was continued for 180 min, and the mixture was extruded at 286°C, dried at 80°C, and sliced to obtain modified polyester fiber slices; (12) The modified polyester fiber slices were pre-crystallized at 200°C, and then dried with dry air with a dew point of -82°C, the drying temperature was 180°C, and the drying time was 12 hours to obtain the pretreated modified polyester fiber slices; the modified polyamide fiber slices were dried at 100°C for 4 hours to obtain the pretreated modified polyamide fiber slices; the pretreated modified polyamide fiber slices and the pretreated modified polyester fiber slices were melt-spun at a mass ratio of 82:18, and the pretreated modified polyamide fiber and the pretreated modified The flow process of the polyester fiber melt in the spinning assembly is as follows: the pretreated modified polyamide fiber goes through the plum blossom groove channel, the pretreated modified polyester fiber goes through the hole channel, and the spinning speed is 3300m / min; the spinning temperature of the pretreated polyamide fiber is 270℃, and the pressure is 15MPa, and the spinning temperature of the pretreated polyester fiber is 295℃, and the pressure is 17MPa; and then it is cooled and formed by side wind at a wind speed of 0.65m / min and a wind temperature of 22℃ to obtain a light-colored light-absorbing and heat-generating composite fiber;.
[0030] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that there are no steps (1) and (3), and step (4) is changed to: porous zinc oxide nanorods and cyclohexanecarboxylic acid are mixed in a mass ratio of 2:1 to obtain a mixture, dissolved in an ether solution 3 times the mass of the mixture, and then 0.05 times the mass of the mixture is added with p-toluenesulfonic acid, 30kHz ultrasound is applied for 80min, the temperature is raised to 78°C, stirred at 700r / min for 6h, filtered to obtain a precipitate, and 3 times the mass of the precipitate The amount of 80wt% acetic acid solution and 0.04 times the amount of cyclohexane are added. cobalt, and then add 50wt% acetaldehyde solution (0.5 times the mass of the precipitate), stir at 300r / min for 30min, react at 90°C and 1.8MPa for 9h, filter while hot, and take the solid; step (5) is changed to: mix the solid, adipic acid, hexamethylenediamine and ethanol in a mass ratio of 1:0.5:2:3, heat to 60°C, stir and mix at 100r / min for 3h, filter, take the precipitate, wash it with ethanol for 3 times, dry it at 80°C for 24h, and add deionized water to prepare a 63wt% aqueous solution; the remaining steps are the same as those in Example 1.
[0031] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that there is no step (4), and step (5) is changed to: adipic acid, hexamethylenediamine and ethanol are mixed in a mass ratio of 1.5:2:3, heated to 60°C, stirred and mixed at 100 r / min for 3 hours, filtered, the precipitate is taken, washed with ethanol for 3 times, dried at 80°C for 24 hours, and deionized water is added to prepare a 63wt% aqueous solution; step (6) is changed to: the above aqueous solution is injected into a static mixer, and 0.5 times the mass of ethylenediamine acetic acid solution is added, wherein the hexamethylenediamine and ethylenediamine acetic acid solution are 1.5:2:3. The molar ratio of acetic acid is 3:5, and modified nano zinc oxide powder with a mass 3 times that of the aqueous solution is added, and then placed in an evaporation reactor, evaporated for 3 hours at 232°C, 1.72MPa and nitrogen protection, then enters a tubular reactor and is heated to 285°C, reacts for 40 minutes, and the pressure is reduced to 0.28MPa for extrusion, enters a finished product reactor, reduces the pressure to 40kPa, reduces the temperature to 270°C, reacts for 50 minutes, extrude at 270°C, dry at 60°C for 20 hours, and slices to obtain modified polyamide fiber slices; the remaining steps are the same as in Example 1.
[0032] Comparative Example 3: Comparative Example 3 differs from Example 1 in that steps (7), (8) and (9) are omitted, and step (10) is changed to: 2,5-dimethylphenol and MC catalyst are poured into a high-pressure reactor in a mass ratio of 15:1, ventilated with nitrogen three times, and then filled with oxygen at room temperature until the pressure reaches 1 MPa, the oil bath is heated to 90°C, stirred at 500 r / min, reacted for 4 hours, naturally cooled to room temperature, filtered, and the precipitate is taken, washed three times with acetic acid 1.5 times the mass of the precipitate, and dried at 100°C for 24 hours to obtain terephthalic acid; the preparation method of the MC catalyst is: Co(OAc)2, Mn(OAc)2 and NaBr are mixed in a molar ratio of 0.13:0.029:1, and dissolved in acetic acid 4.1 times the total mass; step (11) is changed to: The method comprises the following steps: mixing ethylene glycol and terephthalic acid at a mass ratio of 1.05:1 to obtain a mixed solution, adding 100 nm nano titanium oxide powder of 2.05 times the mass of the mixed solution and antimony acetate of 3 times the mass of the mixed solution, stirring at 200 r / min for 2 hours; then heating to 255° C., increasing the pressure to 140 kPa, and reacting for 6 hours; continuing to heating to 264° C., decreasing the pressure to 110 kPa, and reacting for 90 minutes; then continuing to heating to 272° C., decreasing the pressure to 10 kPa, and reacting for 40 minutes; continuing to heating to 375° C., decreasing the pressure to 1 kPa, and reacting for 50 minutes; decreasing the temperature to 284° C., decreasing the pressure to 0.14 kPa, and reacting for 180 minutes, extruding at 284° C., drying at 60° C., and slicing to obtain modified polyester fiber slices; and the remaining steps are the same as those in Example 1.
[0033] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that there are no steps (9) and (10), and step (11) is changed to: ethylene glycol, terephthalic acid and modified nano titanium oxide powder are mixed in a mass ratio of 1.05:1:2.2 to obtain a mixed solution, antimony acetate in an amount 3 times the mass of the mixed solution is added, and stirred at 200 r / min for 2 h; then the temperature is raised to 255°C, the pressure is raised to 140 kPa, and the reaction is carried out for 6 h; the temperature is further raised to 264°C, the pressure is reduced to 110 kPa, and the reaction is carried out for 90 min; then the temperature is further raised to 272°C, the pressure is reduced to 10 kPa, and the reaction is carried out for 40 min; the temperature is further raised to 375°C, the pressure is reduced to 1 kPa, and the reaction is carried out for 50 min; the temperature is reduced to 284°C, the pressure is reduced to 0.14 kPa, and the reaction is carried out for 180 min, and the modified polyester fiber slices are obtained; the remaining steps are the same as those in Example 1.
[0034] Effect example The following table shows the performance analysis results of the fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0035] Table 1 Test results of light absorption and heating effect of Examples 1-3 and Comparative Examples 1-4
[0036] Table 2.1 Dyeing rate and breaking strength test results of Examples 1-3 and Comparative Examples 1-4
[0037] Table 2.2 Antibacterial and radiation resistance test results of Examples 1-3 and Comparative Examples 1-4
[0038] It can be seen from Table 1 and Table 2 that for Comparative Example 1: the pure phase porous nano zinc oxide does not react with the carbon dot solution. Without the catalytic property of carbon dot-zinc oxide, the cyclohexane structure in cyclohexanecarboxylic acid cannot be catalytically oxidized to generate adipic acid, which will affect the subsequent polymerization process to form slices, resulting in the inability to prepare complete slices and making subsequent spinning impossible. In order to ensure normal spinning, adipic acid with a similar structure is used instead of the original cyclohexanecarboxylic acid to prepare slices. It can be seen from Examples 1, 2, 3 and Comparative Example 1 that without modifying the nano zinc oxide with the carbon dot solution, the light absorption and heat generation, heat preservation, dyeing rate, breaking strength, antibacterial properties and radiation resistance of the composite fiber are very poor, indicating that the nano zinc oxide is not surface active and the molecules are easy to agglomerate and not easy to attach to organic matter, which affects the performance of the composite fiber. For Comparative Example 2: the nano zinc oxide modified with the carbon dot solution does not react with cyclohexanecarboxylic acid, so the cyclohexanecarboxylic acid cannot be catalytically oxidized to generate adipic acid, which affects the subsequent polymerization process to form slices, resulting in the inability to prepare complete slices, making it impossible to carry out subsequent spinning. In order to ensure normal spinning, adipic acid with a similar structure is used instead of the original cyclohexanecarboxylic acid to prepare slices. From Examples 1, 2, 3, Comparative Example 1 and Comparative Example 2, it can be seen that the carbon dot solution is used to modify nano zinc oxide, but the modified nano zinc oxide particles are not introduced in advance. Although the light absorption and heating, heat preservation, dyeing rate, breaking strength, antibacterial performance and radiation resistance of the composite fiber are improved, the improvement is not much. It can be seen that the zinc oxide nanoparticles are introduced first and then polymerized to generate fibers, which overcomes the problem that the zinc oxide nanoparticles are easy to agglomerate themselves, making the zinc oxide nanoparticles more evenly distributed in the polyamide fiber. For Comparative Example 3: KH570 is not added to modify nano titanium oxide, which affects the subsequent polymerization process of forming slices, and 2,5-dimethylbenzene loaded with nano titanium oxide powder cannot be generated, resulting in the inability to prepare complete slices, making it impossible to carry out subsequent spinning. In order to ensure normal spinning, 2,5-dimethylphenol with a similar structure is used to replace the original 2,5-dimethylphenol loaded with nano titanium oxide to prepare slices. From Examples 1, 2, 3 and Comparative Example 3, it can be seen that although the light absorption and heating, heat preservation, dyeing rate, breaking strength, antibacterial properties and radiation resistance of the composite fiber are improved, the improvement is not much. Without the modification of the nano-titanium oxide particles with a silane coupling agent, the nano-titanium oxide molecules are easy to agglomerate and are not easy to be grafted with organic matter, which produces a beneficial effect. It can also be seen that the main role in the composite fiber should be played by the nano-zinc oxide particles. The nano-titanium oxide particles only make up for the deficiency of nano-zinc oxide in ultraviolet radiation absorption, improve the light absorption and heating and heat preservation effects, but the surface modification of the nano-titanium oxide particles can still improve the effect of the composite light absorption and heating material.For Comparative Example 4: Nano-titanium oxide modified by KH570 does not react with 2,5-dimethylphenol, which affects the subsequent polymerization process of forming slices, and terephthalic acid loaded with nano-titanium oxide powder cannot be generated, resulting in the inability to prepare complete slices, making it impossible to carry out subsequent spinning. In order to ensure normal spinning, terephthalic acid with a similar structure is used to replace the original terephthalic acid loaded with nano-titanium oxide powder to prepare slices. From Examples 1, 2, 3, Comparative Example 3 and Comparative Example 4, it can be seen that the use of KH570 to modify nano-titanium oxide particles without first introducing titanium oxide nano-particles and then polymerizing to generate fibers, although the light absorption, heat generation and thermal insulation effects of the composite fiber are improved, the improvement is not large, so it is very necessary to first introduce nano-titanium oxide particles and then polymerize to generate polyester fibers.
[0039] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a light-colored light-absorbing and heat-generating composite fiber, characterized in that: The method comprises the following preparation steps: (1) The modified nano zinc oxide powder and cyclohexane carboxylic acid are mixed in a mass ratio of 2 to 3:1 to obtain a mixture, which is dissolved in an ether solution 3 to 5 times the mass of the mixture, and then 0.05 to 0.1 times the mass of the mixture is added with p-toluenesulfonic acid, ultrasonicated at 30 to 40 kHz for 80 to 100 minutes, heated to 78 to 79°C, stirred at 700 to 800 r / min for 6 to 8 hours, filtered to obtain a precipitate, and then 3 to 5 times the mass of the precipitate is added with 80wt% acetic acid solution and 0.04 to 0.15 times the amount of cyclohexane substance. Then, 0.5 to 1 times the mass of the precipitate is added with 50wt% acetaldehyde solution, stirred at 300 to 500 r / min for 30 to 60 minutes, reacted at 90°C and 1.8 MPa for 9 hours, filtered while hot, and the solid was taken out and dried at 100°C for 24 hours to obtain adipic acid loaded with nano zinc oxide particles; (2) Adipic acid, hexamethylenediamine and ethanol loaded with nano zinc oxide particles were mixed in a mass ratio of 1.5:2:3, heated to 60-70°C, stirred at 100-150 r / min for 3 h, filtered, the precipitate was taken, washed with ethanol for 3-5 times, dried at 80°C for 24 h, and deionized water was added to prepare a 63 wt% aqueous solution; (3) The aqueous solution is introduced into a static mixer, and an ethylenediamine acetic acid solution of 0.5 to 0.6 times the mass of the aqueous solution is added, wherein the molar ratio of hexamethylenediamine to acetic acid in the ethylenediamine acetic acid solution is 3:5, and then placed in an evaporation reactor, evaporated for 3 hours at 232°C, 1.72MPa and nitrogen protection, and then entered into a tubular reactor and heated to 285°C, reacted for 40 to 45 minutes, and the pressure was reduced to 0.28MPa for extrusion, and then entered into a finished product reactor, the pressure was reduced to 40kPa, the temperature was reduced to 270 to 272°C, the reaction was 50 to 55 minutes, and the modified polyamide fiber slices were obtained; (4) The modified nano titanium oxide powder and 2,5-dimethylphenol were mixed at a mass ratio of 2.2-2.5:1, phosphorus trichloride (0.6-0.8 times the mass of the mixed solution) was added, and the mixture was stirred at 700-800 r / min for 48 h. The oil bath was heated to 130-135°C and the reaction was carried out for 6-8 h. After the reaction, the temperature was lowered to 110-120°C, and a 5 wt% sodium bicarbonate aqueous solution (3-5 times the total mass of the reaction solution) was poured in. After reacting for 2-3 h, the mixture was filtered and the precipitate was taken out. After drying at 60-80°C for 24 h, the precipitate was recrystallized with ethanol (1.5-2 times the mass of the precipitate), filtered, and dried at 60-80°C for 24 h to obtain 2,5-dimethylbenzene loaded with nano titanium oxide powder. (5) 2,5-dimethylbenzene loaded with nano-titanium oxide powder and MC catalyst were poured into a high-pressure reactor at a mass ratio of 15-20:
1. After nitrogen ventilation for 3 times, oxygen was filled in at room temperature to a pressure of 1 MPa. The oil bath was heated to 90-95°C, stirred at 500-600 r / min, reacted for 4 hours, cooled naturally to room temperature, filtered, and the precipitate was washed 3 times with acetic acid 1.5-2 times the mass of the precipitate, and dried at 100°C for 24 hours to obtain terephthalic acid loaded with nano-titanium oxide powder; (6) Ethylene glycol and terephthalic acid loaded with nano-titanium oxide powder are mixed in a mass ratio of 1.05-1.15:1 to obtain a mixed solution, antimony acetate in an amount 3-5 times the mass of the mixed solution is added, and the mixture is stirred at 200-300 r / min for 2 hours; then the temperature is raised to 255-257°C, the pressure is raised to 140 kPa, and the reaction is continued for 6 hours; the temperature is further raised to 264-266°C, the pressure is reduced to 110 kPa, and the reaction is continued for 90 minutes; then the temperature is further raised to 272-274°C, the pressure is reduced to 10 kPa, and the reaction is continued for 40 minutes; the temperature is further raised to 375-377°C, the pressure is reduced to 1 kPa, and the reaction is continued for 50 minutes; the temperature is further reduced to 284-286°C, the pressure is reduced to 0.14 kPa, and the reaction is continued for 180 minutes, and the mixture is extruded at 284-286°C, dried at 60-80°C, and sliced to obtain modified polyester fiber slices; (7) The pretreated modified polyamide fiber slices and the pretreated modified polyester fiber slices are melt-spun at a mass ratio of 82:18, cooled and formed to obtain a light-colored light-absorbing and heat-generating composite fiber.
2. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The modified nano zinc oxide powder in step (1) comprises the following preparation steps: 1) Take 20-30 mg candle ash and 40-60 g sodium hydroxide and stir at 80-100 r / min for 20-30 min, add 40 mL secondary deionized water, stir at 80-100 r / min for 20-30 min, and ultrasonicate at 30-40 kHz for 30-60 min to obtain a reaction solution, put the reaction solution into a hot air drying oven, heat it to 200 ° C and keep it at a constant temperature for 10-15 h, and then naturally cool it to room temperature; centrifuge at 9000-12000 r / min for 3-5 h to remove the precipitate, adjust the pH to 7-8 with 37 wt% hydrochloric acid solution, and then filter with a 0.20-0.25 um filter membrane to obtain a filtrate, dialyze the filtrate in 4 L secondary deionized water with a MWCO 3500 dialysis bag for 6-8 h, replace 4 L secondary deionized water and dialyze for another 6-8 h to obtain a carbon dot solution; The carbon dot solution was dried at 80°C and 40-50 kPa for 24-30 h to prepare a 190-200 mg / L carbon dot solution; 2) Dissolve 10-15 mmol zinc nitrate hexahydrate and 10-15 mmol oxalic acid dihydrate in 20-30 mL anhydrous ethanol solution, stir at 200-300 r / min for 4-6 h until completely dissolved, then pour the mixed solution containing oxalic acid into the zinc nitrate mixed solution while stirring at 200-300 r / min, heat to 120-150 ° C for 9-12 h, cool to room temperature, collect the solid by centrifugation, wash with deionized water 2-3 times, then wash with anhydrous ethanol 2-3 times, dry at 80 ° C for 20-30 h, calcine the dried solid at 420 ° C for 2-3 h, and naturally cool to room temperature to obtain pure phase porous zinc oxide nanorods; 3) Take 10 g of porous zinc oxide nanorods and put them in 50 mL of distilled water. Ultrasonicate at 30-40 kHz for 10-30 min, add carbon dot solution until the mass fraction of the carbon dot solution is 0.2%-2%, stir at 300-400 r / min for 3-6 h, then wash and centrifuge at 8000-10000 r / min for 3-5 h, and then dry at 100°C for 10-15 h to obtain modified nano zinc oxide powder.
3. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The modified nano titanium oxide powder in step (4) comprises the following preparation steps: a. Place 10 g of titanium oxide powder with a particle size of 100 nm in a vacuum drying oven at 120-130°C and 50-60 kPa for 2-3 hours, then place in 100 mL of anhydrous ethanol solution, and disperse at 30-40 kHz ultrasonic wave for 30-60 minutes to obtain a dispersed nano-titanium oxide ethanol solution; b. Dissolve 5-20 mg of KH570 in 100 mL of deionized water and hydrolyze for 30-60 min to obtain a KH570 aqueous solution. Completely mix the nano titanium oxide ethanol solution obtained in step a and the KH570 aqueous solution obtained above, adjust the pH to 4 with a 35 wt % acetic acid aqueous solution, centrifuge at 10000-12000 r / min for 20-30 min, take the solid, place it in 200-300 mL of deionized water, ultrasonicate at 30-40 kHz for 10-30 min, centrifuge at 10000-12000 r / min for 20-30 min, take the solid, dry it at 100-120 ° C for 20-30 h, and cool it to room temperature under a vacuum of 40-50 kPa to obtain a modified nano titanium oxide powder.
4. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The preparation method of the MC catalyst in step (5) is as follows: Co(OAc)2, Mn(OAc)2 and NaBr are mixed in a molar ratio of 0.13-0.18:0.029-0.033:1, and then dissolved in an acetic acid solution with a total mass of 4.1-4.4 times.
5. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The pretreated modified polyester fiber chips in step (7) are obtained by pre-crystallizing the modified polyester fiber chips at 150-200° C. and then drying them with dry air having a dew point of -82° C., at a drying temperature of 130-180° C., and for a drying time of 6-12 hours.
6. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The pretreated modified polyamide fiber slices in step (7) are obtained by drying the modified polyamide fiber slices at a temperature of 80 to 100° C. for 4 hours.
7. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: In step (7), the flow process of the pretreated polyamide fiber and the pretreated polyester fiber melt in the spinning assembly is as follows: the pretreated modified polyamide fiber flows through the plum blossom channel, and the pretreated modified polyester fiber flows through the hole channel.
8. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: In step (7), the spinning temperature of the pretreated polyamide fiber is 260-270° C. and the pressure is 13-15 MPa, and the spinning temperature of the pretreated polyester fiber is 285-295° C. and the pressure is 15-17 MPa.
9. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The spinning speed of the melt spinning in step (7) is 2800~3300m / min.
10. The method for preparing a light-colored light-absorbing and heat-generating composite fiber according to claim 1, characterized in that: The specific conditions for the cooling forming in step (7) are: side wind cooling with a wind speed of 0.40-0.65 m / min and a wind temperature of 18-22°C.
Citation Information
Patent Citations
Production method of durable anti-ultraviolet chinlon 6 fiber
CN102433602A
Method for preparing modified polyamide composite fiber
CN107829163A
Anti-static fabric and preparation method thereof
CN118390187A
Preparation method for multifunctional plant-sourced composite material used for fiber spinning
WO2024065863A1
